Simulation Study of Quadcopter Altitude Control - ‘Azim, Muhammad; Abd Rahman, Ramhuzaini (Progress in Aerospace and Aviation Technology, 2022)
In this paper, a virtual simulation study of altitude controller which implement the use of PID controller is proposed in order to hover a quadcopter in vertical motion. A complete simulation of a quadcopter to move in a vertical direction is highlighted in this paper. The quadcopter is designed to be used in an enclosed area and its disturbance is neglected Analysis on the values of time and frequency-domain requirement values prevents waste of resources if been done by experimental setup. The desired altitude and actual altitude gained also analyzed in this paper. By using MATLAB software in order to simulate the PID controller and the end result also analyzed by using MATLAB. Finding that can be obtained in this research is the analysis desired and actual altitude obtained by using tuned PID controller. Simulations data such as transient response which gave the value of 3.91s, steady state error is 0 and the overshoot that had value of 13.9% has been achieved in this simulation setup. The objective of this research is to develop a virtual simulation study on quadcopter’s altitude control.